In silico molecular target prediction unveils mebendazole as a potent MAPK14 inhibitor. Issue 12 (18th October 2020) - Ariey‐Bonnet, Jeremy; Carrasco, Kendall; Le Grand, Marion; Hoffer, Laurent; Betzi, Stéphane; Feracci, Mikael; Tsvetkov, Philipp; Devred, Francois; Collette, Yves; Morelli, Xavier; Ballester, Pedro; Pasquier, Eddy
Abstract : The concept of polypharmacology involves the interaction of drug molecules with multiple molecular targets. It provides a unique opportunity for the repurposing of already‐approved drugs to target key factors involved in human diseases. Herein, we used an in silico target prediction algorithm to investigate the mechanism of action of mebendazole, an antihelminthic drug, currently repurposed in the treatment of brain tumors. First, we confirmed that mebendazole decreased the viability of glioblastoma cells in vitro (IC50 values ranging from 288 nm to 2.1 µm ). Our in silico approach unveiled 21 putative molecular targets for mebendazole, including 12 proteins significantly upregulated at the gene level in glioblastoma as compared to normal brain tissue (fold change > 1.5; P  < 0.0001). Validation experiments were performed on three major kinases involved in cancer biology: ABL1, MAPK1/ERK2, and MAPK14/p38α. Mebendazole could inhibit the activity of these kinases in vitro in a dose‐dependent manner, with a high potency against MAPK14 (IC50  = 104 ± 46 nm ). Its direct binding to MAPK14 was further validated in vitro, and inhibition of MAPK14 kinase activity was confirmed in live glioblastoma cells. Consistent with biophysical data, molecular modeling suggested that mebendazole was able to bind to the catalytic site of MAPK14. Finally, gene silencing demonstrated that MAPK14 is involved in glioblastoma tumor spheroid growth and response to mebendazole treatment. This study thus highlighted the role of MAPK14 in the anticancer mechanism of action of mebendazole and provides further rationale for the pharmacological targeting of MAPK14 in brain tumors. It also opens new avenues for the development of novel MAPK14/p38α inhibitors to treat human diseases. Abstract : Drug polypharmacology was explored in silico to identify novel molecular targets of antihelminthic drug mebendazole, currently repurposed for the treatment of brain cancers. By combining transcriptomic analysis, molecular docking, and functional assays (biophysical, biochemical, and cellular), we validated MAPK14 as a critical target of mebendazole and a key player in glioblastoma progression.